The re-examination of the effects of strategic similarities on post-merger performance: a study of European banks - Truong, Hien Dang (2015)
This study attempts to contribute to a handful of research on the impact of strategic relatedness on bank post-merger performance. We employ a dataset of 256 domestic and 61 cross-border M&A transactions with bidders and targets both are European Union banks. Our sample period spans from 2002 to 2011, which contains the latest information and hence provides the most updated analysis. We also obtain a set of financial data that are able to capture the variety of strategic aspects of financial organisations including liquidity, efficiency, loan ratio, capital structure, credit risk, diversity of earnings and off-balance sheet activities. Our independent variables are then derived from such financial data to describe the similarities/differences in each specific strategic area. By utilising two alternative regression methods, we find that the majority of our employed strategic characteristics exhibit positive heterogeneities although the sizes of the effects are lesser for domestic acquisitions in some cases. In addition, we identify the two most prominent reasons for consolidation which are efficiency gain and revenue enhancement. They are in turn indicated by efficiency and earning strategies of individual bank respectively. In terms of efficiency, positive similarity exists although the effect is ambiguous, trivial and appears stronger in case of domestic M&As. With respect to earnings strategies, evidence strongly suggests that differences in such strategies improve post-merger performance, and the size of the impact appears greater for cross-border M&As. The outcomes of this study might imply a new trend in bank M&A activities with a shift in potential targets from ones exhibiting strategic relatedness to ones demonstrating positive differences.